Chińskie zwyczaje pogrzebowe: powtórny pochówek - Muchowska, Joanna (Investigationes Linguisticae, 2018)
The article is devoted to the Chinese death ritual of a secondary burial in its traditional form, known from ancient written sources. It depicts its origin and the most important practices associated with it. The article is based on the BA thesis “Funerary customs in China and Taiwan: secondary burial”, written by the author under the supervision of dr. Marcin Jacobi in the Department of Chinese Language at Warsaw University in 2013.